The Impact of Green Accounting, Environmental Disclosure, and Company Characteristics on Firm Value - Nisaa, Rizka Khoirotun; Hidayati, Cholis (Jurnal Bisnis Mahasiswa, 2025)
This research examines the impact of green accounting, environmental disclosure, and company characteristics on firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2023 period. A quantitative approach was used with a sample of 25 companies, analyzed using SmartPLS 4.1. The results show that green accounting and environmental disclosure do not significantly impact firm value due to the lack of understanding and consistent implementation, particularly in developing countries, and investors' focus on financial indicators. Additionally, SDG disclosure often reduces a company's appeal, being seen as an added cost with no short-term benefits and possibly leading to "greenwashing" concerns. In contrast, company characteristics significantly impact firm value, as they reflect stability and higher profit potential for investors. This research is expected to provide valuable implications for stakeholders, including investors, regulators, and companies. Understanding the factors influencing firm value can help companies take strategic actions to improve their financial and environmental performance.